Numerical investigation of the effect of air supply and oxygen enrichment on the biomass combustion in the grate boiler. (25th June 2019) - Zhou, Anqi; Xu, Hongpeng; Tu, Yaojie; Zhao, Feiyang; Zheng, Zhiming; Yang, Wenming
Highlights: The effect of different air supply on the performance of grate boiler is researched. Raising the ratio of primary air to 43% improves the combustion efficiency clearly. Adjusting the primary air supply in last two zones relates to fuel property. The optimal excess air ratio can be acquired based on numerical simulation. The combustion behavior under oxygen enrichment is investigated. Abstract: The characteristics of biomass combustion in industrial scale grate boiler under different operating conditions are investigated based on the numerical model. On account of the one-dimensional dynamics assumption, a fuel bed model is developed to simulate the biomass incineration on the grate bed, while interacting with three-dimensional CFD furnace model to provide a thoughtful representation of the whole boiler. The model validation is performed based on the experimental data and is used as the standard basis for further investigation. The effect of air supply is analyzed with a combination of numerical results and efficiency analysis. Under constant excess air ratio, the thermal efficiency of the boiler is raised greatly when the primary air supply is elevated to 43% of the total air supply, but the improvement is limited when the ratio of primary air is further increased to 50%. The influence of redistribution of primary air supply in zone 4 and zone 5 on the thermal efficiency is dependent on the conversion rate of fuel in the first three zones, although the bottom ash temperature can be reduced through increasing the air flow in zone 5. An increase in excess air ratio contributes to better burnout but stack loss increase simultaneously, so an optimum ratio is found to be 1.6. Oxygen-enriched combustion is also explored in this study. The combustion improves obviously by enriching the volume fraction of O2 in primary air to 25%, and the highest temperature in the grate bed is below 1400 K, which is the limitation from the design specification of this commercial grate boiler.